Cataract surgery barrier model: A framework for intervention of cataract blindness in Malaysia - Abdul Mutalib, Othman; Asma', Hassan; Nurulain, Mat Zin; Ahmad, Shahir (2019)
Surgery can easily cure and prevent blindness due to cataract. However, cataract still poses a major public health problem as the single most common cause of global blindness. Identifying the barriers to access cataract surgery is essential to effectively address this problem. By utilising the interpretative phenomenological analysis approach in this study, we identified barriers at the personal, primary care and specialist care level. Based on these findings, a model is designed to better understand and improve the strategy to address the barriers to improve the uptake of cataract surgery in order to prevent cataract blindness in Malaysia.